Non-solar abundance ratios trends of dEs in the Fornax Cluster using newly defined high-resolution indices. Issue 3 (3rd August 2022) - Şen, Şeyda; Peletier, Reynier F; Vazdekis, Alexandre
ABSTRACT: We perform a detailed study of the stellar populations in a sample of massive Fornax dwarf galaxies using a set of newly defined line indices. Using data from the Integral Field Spectroscopic data, we study abundance ratios of eight dEs with stellar mass ranging from 10 8 to 10 9.5 M⊙ in the Fornax Cluster. We present the definitions of a new set of high-resolution Lick-style indices to be used for stellar population studies of unresolved small stellar systems. We identify 23 absorption features and continuum regions, mainly dominated by 12 elements (Na, Ca, Sc, Ti, V, Cr, Mn, Fe, Ni, Y, Ba, and Nd) in the wavelength range 4700–5400 Å and characterize them as a function of age, metallicity, and alpha element abundance ratios. We analyse eight dEs and interpret the line strengths, measured in our new high-resolution system of indices, with the aid of stellar population models with high enough spectral resolution. We obtain abundance ratio proxies for a number of elements that have never been studied before for dwarf ellipticals outside the Local Group. These proxies represent relative deviations from predicted index strengths of base stellar population models built-up following the abundance pattern of The Galaxy. The abundance proxy trend results are compared to abundance ratios from resolved stars in the Local Group, and indices from integrated light of larger early-type galaxies. We find that all our dwarfs show a pattern of abundance ratios consistent with the disc of the Milky Way, indicative of slow formation in comparison to their high-mass counterparts.